(untitled) - Seyler, Dorothy U. (Boston, 2010)
This text still unites instruction in critical reading and analysis, argument, and research strategies with a rich collection of readings that provide both practice for these skills and new ideas and insights for readers.
Keywords: English language,Ngôn ngữ Anh; Rhetoric,Tu từ học